INFLUENCE OF JOB COMPETENCE ON EMPLOYEE’S PERFORMANCE IN PRIVATE UNIVERSITIES IN KENYA - Kamau, Mary Wangari; Mbugua, Dr. Doris (IJRDO - Journal of Business Management, 2018)
Human assets are one of the most important resources available to any organization. The demand for effective employees continuously increases both in private and public universities. This is because employee competence and commitment largely determine the objectives that an organization can set for itself and to its success in achieving them. The study sought to determine the influence of job competence on employee’s performance in private universities in Kenya. The research study adopted a descriptive survey design which was based on the use of a questionnaire. The population of the study included all the 35 private universities in Kenya. The data was collected using questionnaires from employees of private universities in Kenya. Correlation analysis and regression analysis were conducted as the key analytical tools. The results showed that there was a strong positive relationship between job competence on employee’s performance in private universities in Kenya. The study recommends that the universities should place emphasis on the influence of job competence in order to enhance employee’s performance and competiveness.